Review of Energy Efficiency of the Gas Production Technologies From Gas Hydrate-Bearing Sediments - Yamamoto, Koji; Nagakubo, Sadao (Frontiers in Energy Research, 2021)
Even in the carbon-neutral age, natural gas will be valuable as environment-friendly fuel that can fulfill the gap between the energy demand and supply from the renewable energies. Marine gas hydrates are a potential natural gas source, but gas production from deposits requires additional heat input owing to the endothermic nature of their dissociation. The amount of fuel needed to produce a unit of energy is important to evaluate energy from economic and environmental perspectives. Using the depressurization method, the value of the energy return on investment or invested (EROI) can be increased to more than 100 for the dissociation process and to approximately 10 or more for the project life cycle that is comparable to liquefied natural gas (LNG) import. Gas transportation through an offshore pipeline from the offshore production facility can give higher EROI than floating LNG; however, the latter has an advantage of market accessibility. If the energy conversion from methane to hydrogen or ammonia at the offshore facility and carbon capture and storage (CCS) can be done at the production site, problems of carbon dioxide emission and market accessibility can be solved, and energy consumption for energy conversion and CCS should be counted to estimate the value of the hydrate resources.